Technological Capability as a Determinant of FDI Inflows: Evidence from Developing Asia & India - Amitendu Palit; Shounkie Nawani (Indian Council for Research on International Economic Relations (ICRIER), 2007)
This paper contributes to the empirical literature on determinants of FDI by addressing the question: Why do some developing countries from Asia continue to receive more FDI, while others from the region have fallen behind? It finds R&D-based innovative capacities, and the ability to apply such capacities through modern IT-based techniques, as the two key determinants explaining FDI inflows to developing Asian economies. These traits are found significant for inward FDI in India too with more technology intensive sectors receiving greater FDI. The findings of the paper suggest that in the absence of strong technological foundations and well-developed communications infrastructure, liberal policies alone are not enough for drawing FDI, once initial advantages, like cheap labour, fizzle out. For developing countries like India, strong thrust on R&D and innovative skills is needed for attracting FDI in technology-intensive exports. Therefore, policy actions would have to go further than a broad-based opening up of sectors to FDI, and increasing the limit of such investment in these sectors, for sustained inflows of FDI.
Keywords: F21; L86; O3; 330; FDI inflows; technology and technological capabilities; locational advantages; IT-based communication facilities; Auslandsinvestition; Wirkungsanalyse; Technischer Fortschritt; Schätzung; Asien